2016
DOI: 10.1002/jbm.a.35942
|View full text |Cite
|
Sign up to set email alerts
|

Construction and histological analysis of a 3D human arterial wall model containing vasa vasorum using a layer‐by‐layer technique

Abstract: There is considerable global demand for three-dimensional (3D) functional tissues which mimic our native organs and tissues for use as in vitro drug screening systems and in regenerative medicine. In particular, there has been an increasing number of patients who suffer from arterial diseases such as arteriosclerosis. As such, in vitro 3D arterial wall models that can evaluate the effects of novel medicines and a novel artificial graft for the treatment are required. In our previous study, we reported the rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Previous reports were consulted for ultrastructural analyses using transmission electron microscopy (TEM) 41 . Briefly, iPSC-CM 3D-tissues in in vitro and resected rat hearts were fixed with 2.5% glutaraldehyde and 1% PFA in 0.1 M phosphate buffer (PB) containing 0.01% CaCl 2 and MgCl 2 , and cut into small tissue pieces.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports were consulted for ultrastructural analyses using transmission electron microscopy (TEM) 41 . Briefly, iPSC-CM 3D-tissues in in vitro and resected rat hearts were fixed with 2.5% glutaraldehyde and 1% PFA in 0.1 M phosphate buffer (PB) containing 0.01% CaCl 2 and MgCl 2 , and cut into small tissue pieces.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, physical stress can be avoided by resorting to filtration‐assisted LbL technology which assures high viability and efficiency to the FN/G coated cells. The filtration‐assisted LbL methodology has been employed to engineer 3D human tissue constructs, including vascularized cardiac microtissues, liver, and blood vessels . Using a different approach, researchers also demonstrated that the LbL assembly technology can be combined with automatic inkjet printing of single cells and ECM proteins to precisely develop 3D human microtissue chips in a rapid and automatic mode .…”
Section: Cell–biomaterials Assembliesmentioning
confidence: 99%
“…[ 135 ] In this fashion, living material constructs are created in which biomaterials initiate composite assembling, after which, cells and cellular assemblies can partake in biological complexities. In order to guide such organization, biomaterials have been employed in the form of microgels, [ 136 ] microparticles, [ 19b,71b ] nanoparticles, [ 71c,137 ] and multilayer film architectures. [ 71a,138 ] A relevant challenge among these systems is the relative difficulty found in securely regulating the assembly process so as to achieve specific scales of assembly or assembly shapes.…”
Section: Composite Living Materialsmentioning
confidence: 99%
“…[ 18b,66a,b,70 ] In addition to directly assembling composite constructs, the added material may itself play a role in driving composite assembly. For example, cell surfaces may be functionalized with thin material layers or objects which promote aggregation, [ 71 ] and cells themselves may be directly attached to larger material building blocks that confer cues of assembly or aggregation. [ 72 ] Composites created using these techniques have been implemented in areas such as biosensing, [ 73 ] water‐treatment, [ 74 ] bioremediation, [ 2b,75 ] drug delivery, [ 76 ] energy, [ 77 ] bioproduction, [ 78 ] “smart packaging,” [ 79 ] tissue engineering, [ 80 ] immune engineering, [ 81 ] and cell encapsulation.…”
Section: Composite Living Materialsmentioning
confidence: 99%
See 1 more Smart Citation